A contribuição da literatura infantil para as práticas de letramento: primeira fase do ensino fundamental - Brandão, Viviane Gomes (Universidade Federal do Tocantins, 2020)
This work reflects on the contribution of children's literature for literacy practices, prioritizing the first stage of the elementary school. Is based on an action research, which aims to investigate the development of literacy practices from the work developed with children's literature. The investigation is performed from the application of a Didactic Unit (UD), with development in a fifth-grade class in a school Hall in Araguaína. The Didactic Unit includes interaction activities around the collective reading of the book: the hen Redhead, author: Editora FTD, Magical Book Collection. As a final product of UD, was suggested the construction of a children's book and a presentation of a dramatization, productions and records of the students involved. The proposal for analysis of the data acquired is the literacy perspective, giving priority to reading and writing, whereas the oral and written language development, acquisitions, proposed by VIGOTSKY (2008), as well as the awakening of taste for reading, debates, music and interaction between teacherresearcher and students. In this follow-up, a way of thinking the child as protagonist of the learning process, as the role of literature in school, like language alive, dynamic and mobilizing knowledge and subject.